Additional viruses - Morales, Francisco José; Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1989)
Bean crops are attacked by several viruses transmitted by insects among which are: (1) beet curly top virus (Circulifer tenellus); the best control measure is the utilization of resistant var.; (2) the tobacco yellow dwarf virus (Orosius argentatus); (3) the tomato spotted wilt virus, which is transmitted mechanically and by various types of thrips; and (4) the tobacco streak virus, which is transmitted mechanically in the seed and by thrips. Insect vectors have not been reported; it can be controlled using resistant var. Other viral diseases of beans include peanut stunt, cowpea severe mosaic, tobacco ringspot, and tobacco necrosis. (CIAT)